2020
DOI: 10.1371/journal.pone.0227716
|View full text |Cite
|
Sign up to set email alerts
|

Allele specific expression of Dof genes responding to hormones and abiotic stresses in sugarcane

Abstract: Dof transcription factors plant-specific and associates with growth and development in plants. We conducted comprehensive and systematic analyses of Dof transcription factors in sugarcane, and identified 29 SsDof transcription factors in sugarcane genome. Those SsDof genes were divided into five groups, with similar gene structures and conserved motifs within the same groups. Segmental duplications are predominant in the evolution of Dof in sugarcane. Cis-element analysis suggested that the functions of SsDofs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…2 ). The quantity of SoDofs is lower than that of Arabidopsis (36) 27 , tomato (34) 42 , wheat (96) 43 , rice (30) 27 , potato (35) 44 , soybean (78) 28 , and sugarcane (29) 31 , but it is same to that of sugarbeet. This is because spinach separated with Arabidopsis just after the ancient whole-genome triplication and there was no whole-genome duplication in spinach genome 1 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…2 ). The quantity of SoDofs is lower than that of Arabidopsis (36) 27 , tomato (34) 42 , wheat (96) 43 , rice (30) 27 , potato (35) 44 , soybean (78) 28 , and sugarcane (29) 31 , but it is same to that of sugarbeet. This is because spinach separated with Arabidopsis just after the ancient whole-genome triplication and there was no whole-genome duplication in spinach genome 1 .…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, with the sequencing of genome, the identification of Dof genes was widely researched in various plant species, such as Arabidopsis , rice 27 , soybean 28 , maize 29 , sorghum 30 , sugarcane 31 , and so on. The spinach draft genome was reported in 2017 1 , however, few gene families were analyzed for the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Allele-specific expression adds another layer to the complexity of interpreting gene expression in both autopolyploids and allopolyploids. For sugarcane, this phenomenon was investigated in genes with known functions (Cai et al ., 2020; De Mendonça Vilela et al ., 2017). As we evaluated a larger set of expressed genes, the ASEGs found in our study were associated with a wide range of functional roles, mostly with high level metabolic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Allele expression has also been studied in combining the S. spontaneum genome (Zhang et al ., 2018) and transcriptomic datasets. Recently, Cai and colleagues (Cai et al ., 2020) used the upstream region of Dof transcription factors and found cis -elements associated with different functions in plants. Furthermore, these authors identified differences in upstream regions of the alleles of the same gene coding for a transcription factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation